Inside Cover: Rational Design of Zinc/Zeolite Catalyst: Selective Formation of p‐Xylene from Methanol to Aromatics Reaction (Angew. Chem. Int. Ed. 10/2022). Issue 10 (4th February 2022) - Wang, Ning; Li, Jing; Sun, Wenjing; Hou, Yilin; Zhang, Lan; Hu, Xiaomin; Yang, Yifeng; Chen, Xiao; Chen, Congmei; Chen, Biaohua; Qian, Weizhong
Abstract : Hollow triple‐shelled Zn/MFI single crystals were designed by Ning Wang and co‐workers in their Research Article (e202114786) . They exhibit a rather long lifetime as well as an enhanced shape selectivity for p ‐xylene.